Communication for heath behavior change: experiences lived at the Center for Communication Programs at Johns Hopkins University. - Ana Carolina de Oliveira Monteiro dos SANTOS (Universidade de Brasília, 2016)
Sharing experiences is the best way to learn and contribute to the construction of knowledge. It is with this intention that arises this article, a result of the lived experience of the author in workshop taught by the Center for Communication Programs - CCP (Communication Programs Center) at Johns Hopkins University in Baltimore, USA, in June 2014. In this workshop intensive of 20 days, with daily classes full-time, the author had the opportunity to study and share experiences with great thinkers and professionals from Johns Hopkins. This promoted contact with the philosophy of the institution and the methodologies they developed and implemented in countries around the world, in order to promote improvements in the health status of populations through strategic planning focused on behavior change communication. This was an experience not just in study and planning communication, but a leadership training experience, withmore aware, engaged and complete professionals and, above all, of self-knowledge and personal growth. An article would not be enough to describe all this experience, so we chose to focus on issues about the institution's vision on health, the practice of health communication, behavior change and an overview of the essential aspects the methodology developed and used by them, called P process. In this article, the reader will come across a breach of academic theoretical reflections promoted by further technical discussions practices, managerial characteristics. This ends up reflecting the logic implemented by the CCP, which develops the practice based on a broad theoretical framework. And in the same way that the institution does not close in their theories and allows to reinvent itself, this article will also feature the author's own reflections about some of the issues presented.